Online Teaching Evaluation Items (OTEI) and Guidelines For Online Practicum Evaluation (GOPE) / Hamimah Hashim ... [et al.] - Hashim, Hamimah; Abdullah, Nabilah; Syed Mustafa, Sharifah Muzlia; Hamzah, Lina Mursyidah; Mohd Yusof, Norhayati; Wan Yunus, Farhana; Syed Aris, Sharipah Ruzaina (2020)
Online Teaching Evaluation Items (OTEi) and Guidelines for Online Practicum Evaluation (GOPE) are two significant evaluation documents produced during the Restricted Movement Order (RMO) due to changes in the nature of Practicum assessment. OTEi is an assessment tool consisting of 20 items that evaluate trainees’ online teaching performances while GOPE is a comprehensive guide for lecturers, mentors and trainee teachers on the evaluation of the online teaching performances. Items in OTEi were developed based on the need analysis and interview with several teachers and lecturers. This assessment tool is important to assess trainee teachers’ competency in planning, conducting, facilitating online session and professional responsibilities. GOPE consists of 16 pages that illustrate the practicum processes and dates, evaluation weightage, online classes, components and scale for online teaching evaluation, calculation for overall marks for lecturers and mentors and information on Post Practicum. Both documents established systematic basis for online teaching observation and evaluation that is as equitable as possible for all disciplines and styles of teaching. OTEi and GOPE received positive remarks from lecturers, mentors and trainee teachers. These evidence-based practices were presented at The Second Bukit Tinggi International Conference on Education (BICED) 2020 on 14 Sept 2020, by Dr Hamimah Hashim who was invited as a speaker to share the best practices for online practicum. OTEi and GOPE are aligned with our National Education Philosophy and synchronized with Twelfth Malaysia Plan (2021-2025), to adopt and innovate digital technologies, productivity and quality of life, and finally support Sustainable Development Goals (SDG) which aim to provide quality education to all.